Management of Authentic Learning Strategies to Improve Children's Thinking Abilities - Syamsuddin; Muhammad Fadhli; Suwandi Simangunsong (Yayasan Zia Salsabila, 2024)
Many previous studies have discussed efforts to improve children's thinking abilities, but no one has discussed managing authentic learning strategies. This research aims to describe the management of authentic learning strategies to improve children's thinking abilities. The type of research used is a qualitative approach with descriptive study methods. Data collection through interviews, observation and documentation studies. Data analysis uses reduction, display and conclusion techniques. The results of this research conclude that authentic learning strategies can help improve children's thinking abilities, namely in the form of student coaching that is directly put into practice by teachers, student-centered and problem-solving oriented learning, contextual project-based learning, and extra involvement for students to gain impressive learning experiences. Likewise, in practice authentic learning strategies also experience problems with textual learning content, and require complete learning facilities. Through this research, it is hoped that teachers can measure economic needs, strategic teaching, and interesting content that can be practiced during authentic learning strategies.